IMPROVING STUDENT’S CRITICAL THINKING SKILLS THROUGH GUIDED DISCOVERY LEARNING TO STASIONARY WAVE - AL SISKA, VIRLINDA; RASID ACHMADI, HAINUR (Inovasi Pendidikan Fisika, 2018)
Abstract Student?s critical thinking skills are important skills in learning. Indicators of critical thinking in this study consisted of four indicators. The result of observation in SMAN 1 Gedangan shows only one critical thinking indicator has been reached is an indicator interpretation. Therefore, the research was related the application of guided discovery learning to describe the implementation of learning, improved critical thinking skill, and the response of students to stationary wave. This research used experimental method with pre-experimental design and type of this research is one group pre-test post-test design using one experiment class and two replication class. The implementation of the three class observed from the teacher activity was stated to be very well executed. Based on the analysis of n-gain, critical thinking skills in the experimental class and the replication class 2 increased with medium category. The learning process get positive response from the students with very good category. The critical thinking skill that gets the lowest increase is the interpretation. Overall learning by applying the guided discovery model can improve critical thinking skills of students. Keywords: guided discovery learning, critical thinking skill, stationary wave